SANITARY INSPECTIONS IN ENDOSCOPY CLINICS IN THE STATE OF CEARÁ - Dias Pereira de Oliveira, Géssika; Pinto, José Reginaldo; de Arruda Pedrosa, Kamyla; Farias Pinto, Régila Maria; Pimentel Ferreira Ribeiro, Alanne; Ferreira, Verena Emmanuelle Soares (Cadernos ESP, 2026)
Introduction: Reusable endoscopes pose significant risks of microbial contamination, despite being widely used as diagnostic tools in medical practice. Objective: To describe the main nonconformities identified during sanitary inspections conducted in private endoscopy services. Methods: This is an experience report carried out in a municipality in the interior of the state of Ceará, Brazil, from 2023 to 2025. Results: The inspections revealed advances in structural and care-related aspects; however, they also identified relevant shortcomings related to endoscope reprocessing, the absence of formal records of cleaning and disinfection, deficiencies in staff training, and inadequacies in physical infrastructure. Biosafety conditions and waste management practices were also found to be inconsistent, requiring continuous improvement. Conclusion: It is concluded that inspection and technical monitoring are essential tools for ensuring the quality and safety of endoscopy services, contributing to the promotion of safer environments for both professionals and patients.
Keywords: Endoscopy; Sanitary Surveillance; Patient Safety; Disinfection; Health Services